Analysis of risks in a Learning Management System: A case study in the Spanish National University of Distance Education (UNED) - Esteban Vázquez Cano; M.ª Luisa Sevillano García (Springer, 2015)
This article presents a research that examines the university students' risk perception when using a Learning Management System called "aLF" and implemented by the Spanish National University of Distance Education (UNED) for the development of its university distance studies. The development of comprehensive Learning Management Systems for teaching-learning distance practices in the European Higher Education Area (EHEA) is a challenge for universities all around Europe. For this reason, it is necessary to analyze not only the benefits that involve these environments but the risks perceived by its users to improve teaching methods and design better user interfaces. Through a quantitative method, we test 588 students' opinions about their risks perceptions when using this LMS to study the University degree in Pedagogy. Results show that main risks are concentrated in two dimensions: dimension 1 "basic or general" with high incidence of "fear of making mistakes" and "ignorance of the course content; and dimension 2 "own and beyond students' circumstances" where it is important to stand out the risks not directly controlled by the students: "warning from the authorities for not developing the program", "isolation from teachers" and "delegation of control".